2022
DOI: 10.1001/jama.2022.2832
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sotrovimab on Hospitalization or Death Among High-risk Patients With Mild to Moderate COVID-19

Abstract: IMPORTANCEOlder patients and those with comorbidities who are infected with SARS-CoV-2 may be at increased risk of hospitalization and death. Sotrovimab is a neutralizing antibody for the treatment of high-risk patients to prevent COVID-19 progression.OBJECTIVE To evaluate the efficacy and adverse events of sotrovimab in preventing progression of mild to moderate COVID-19 to severe disease.DESIGN, SETTING, AND PARTICIPANTS Randomized clinical trial including 1057 nonhospitalized patients with symptomatic, mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
258
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(279 citation statements)
references
References 31 publications
20
258
1
Order By: Relevance
“…Our study adds to the main prior clinical trial demonstrating sotrovimab efficacy that had limited sample size (n=583), occurred prior to the emergence of the Delta variant, and was underpowered to evaluate the impact of sotrovimab on patient mortality. [4] This data on the effectiveness of sotrovimab to prevent severe COVID-19 disease induced by the Delta variant may be critical given the unpredictable nature of the COVID-19 pandemic. When combined with in vitro data that suggests sotrovimab effectively neutralizes the omicron variant, [20] these data support continued sotrovimab prioritization among outpatient treatment options.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study adds to the main prior clinical trial demonstrating sotrovimab efficacy that had limited sample size (n=583), occurred prior to the emergence of the Delta variant, and was underpowered to evaluate the impact of sotrovimab on patient mortality. [4] This data on the effectiveness of sotrovimab to prevent severe COVID-19 disease induced by the Delta variant may be critical given the unpredictable nature of the COVID-19 pandemic. When combined with in vitro data that suggests sotrovimab effectively neutralizes the omicron variant, [20] these data support continued sotrovimab prioritization among outpatient treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Several mAb products have received emergency use authorization (EUA) from the US Food and Drug Administration [2] based on Phase II/III randomized clinical trials conducted earlier in the pandemic that demonstrated efficacy towards reduced hospitalization and disease severity among high-risk outpatients. [3][4][5] Use of mAb products such as sotrovimab for individuals who have recently tested positive for SARS-CoV-2 in the outpatient setting is critical to mitigate virus-driven impact on the health care system and is also an evidence-based treatment strategy to improve COVID-19 outcomes among high-risk individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We repeated viral load measurements 7-8 days after monoclonal antibody infusion according to previously published studies reporting on monoclonal antibody therapy. 21 , 22 …”
Section: Methodsmentioning
confidence: 99%
“…The electronic literature search identified a total of 4 studies 4 , 5 , 6 , 7 comprising of 3866 adult patients with COVID-19, including 1040 in the sotrovimab (administered alone) and 2826 in the control group arm, were included in this meta-analysis. The patient demographics and baseline disease characteristics of the study population are shown in Table 1 .…”
mentioning
confidence: 99%